Znaczenie i funkcja mediów w kampanii wyborczej na przykładzie wyborów prezydenckich w USA - Cięciwa, Przemysław (My University, 2013)
Celem pracy było przedstawienie znaczenia i funkcji mediów w kampanii wyborczej na przykładzie wyborów prezydenckich w USA. Pierwsza część pracy opisuje rolę oraz funkcję mediów w tym procesie. Kolejna część to opisanie kampanii wyborczej opartej na marketingu politycznym oraz wyjaśnienie terminów z tym związanych. Ostatnia część opisuje cechy systemu wyborczego w USA oraz analizę SWOT.

Main objective it was show meaning and function of media in election campaign on example presidential election in USA The first part of the work is describing the role, and the post of media in this process. A next section is describing the election campaign based on the political marketing, and explaining terms associated with it. The last part is describing features of the electoral system in USA, and the SWOT analysis.
Meaning and the function of media in an election campaign on the example of presidential elections in the USA
Keywords: marketing polityczny; wybory prezydenckie; kampania; media; political marketing; presidential elections; campaign; media